THE EFFECTIVENESS OF GAMIFICATION IN BIOLOGY LEARNING ON STUDENTS’ MOTIVATION AND HIGHER ORDER THINKING SKILLS: A SYSTEMATIC LITERATURE REVIEW - Rachmani Maulidia; Dewiantika Azizah (Universitas Muhammadiyah Cirebon, 2025)
The advancement of digital technology in the era of the Industrial Revolution 4.0 toward Society 5.0 demands a transformation of learning practices toward student-centered approaches and the development of 21st-century competencies, including learning motivation and Higher Order Thinking Skills (HOTS). In Biology education, which is often abstract and conceptual, innovative strategies are required to enhance student engagement and conceptual understanding. This study aims to systematically analyze the effectiveness of gamification in Biology learning on students’ motivation and HOTS. A Systematic Literature Review (SLR) approach was employed by examining indexed articles published between 2020 and 2025 retrieved from Google Scholar, ERIC, Scopus, and ScienceDirect. Article selection followed PRISMA guidelines based on explicit inclusion and exclusion criteria. Data were analyzed using content analysis and synthesized narratively. The findings indicate that gamification consistently improves students’ learning motivation through elements such as points, badges, leaderboards, challenges, progression levels, and immediate feedback. Gamification also positively impacts HOTS, particularly when designed with contextual problem-based and reflective activities. However, its effectiveness strongly depends on the depth of pedagogical design. Supporting factors include students’ technological readiness and structured instructional integration, while challenges involve limited infrastructure and teachers’ competency in designing meaningful gamified activities. Therefore, gamification has strong potential as a strategic pedagogical approach to enhance Biology learning quality and foster 21st-century competencies.